URBAN SOCIETY IN ROANNE VAN VOORST’S NOVEL TEMPAT TERBAIK DI DUNIA - Intan Maulina; Bilferi Hutapea (Universitas Islam Sumatera Utara (UISU), 2019)
This research is aimed at showing urban society focusing on the social aspects taking place at Bantaran Kali. The social aspects cover economic, political, econimic, religious, criminal and cultural aspects prevailing in the urban society at Bantaran Kali reflected in Roanne Van Voorst’s novel, Tempat Terbaik di Dunia. This research was conducted by using the sociology of literature approach, and the data analysis technique used in this study was genetic structuralism methods. The research results shows that the economic aspects focusing on the conditions of the people who glorify those who have Portofon, and those of the poor at Bantaran Kali were clearly reflected in chapters 1 and 2. Then in chapters 2 and 3, the story of the government's ignorance of the Bantaran people was vividly exposed. In these chapters, the thick political aspects which ultimately cause disasters and harm to other communities were illustrated in detail manners. In chapter 4, the economic aspects and poverty were again the most reflected aspects of the whole chapters, where the people of Bantaran Kali must accept the unfortunate fate that befalls them. Then, the religious aspect was described in chapter 5, and the criminal aspects taking place at Bantaran Kali were clearly reflected in chapter 6. The cultural aspect was illustrated in in chapter 7.